Convergence of blockchain technologies and public administration: a tokenization model for post-war ecosystem restoration - LuhovenkoNataliia Viktorіvna; Ostapko, Iryna (Pressing Problems of Public Administration, 2025)
This article examines a critical issue for Ukraine: the restoration of damaged bioresource potential resulting from military actions through the implementation of innovative tokenization mechanisms. In conditions of limited budgetary resources, where traditional models of state funding prove incapable of innovative breakthroughs, alternative approaches to attracting private capital gain particular significance. The methodological foundation of the research is an interdisciplinary approach that integrates theoretical concepts of decentralized information platforms, platform economics, and noninstitutional theory. Based on an analysis of global experience, six primary models of bioresource tokenization have been identified, and their key components determined: technological verification infrastructure, legal framework, community participation mechanisms, integration with public administration, and a hybrid approach to monetization. A conceptual model of interaction between public administration bodies at various levels and private investors has been developed, based on the principle of a “regulatory perimeter,” where public administration functions as a regulatory facilitator rather than a direct operator of tokenization processes. The research substantiates that cultivating paulownia, a fast-growing species with high carbon sequestration capacity, in affected territories using tokenization technologies can provide a projected profitability of 80-120% over a six-year cycle with investment fractionalization and democratization of access. Four groups of potential risks (regulatory-legal, technological-infrastructural, ecological-economic, and social-institutional) have been structured, and a comprehensive approach to their mitigation has been developed. The study demonstrates that the proposed model allows transforming the role of public administration from direct management to creating a favorable environment for synergy between state and private efforts, ensuring balance between economic growth, environmental sustainability, and social justice. The research results can be used in developing state strategies for restoring affected territories, forming the institutional and legal framework for natural resource tokenization, and implementing pilot public-private partnership projects in bioresource potential restoration.